2015
DOI: 10.1007/s11882-015-0529-x
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Type 2 Endotype in Allergy and Asthma: From Laboratory to Bedside

Abstract: Better management of allergic diseases needs a sharpened understanding of disease heterogeneity and mechanisms in relation to clinically significant outcomes. Phenotypes describing observable clinical and morphologic characteristics and unique responses to treatment have been developed; however, they do not relate to disease mechanisms. Recently, extended heterogeneous and disease-related metabolic, inflammatory, immunological, and remodeling pathways have been described, and reproducible patterns are defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 75 publications
2
57
0
4
Order By: Relevance
“…However, in the past decade, it has become clear that the innate immune cells are critical for the development of asthma and related [33][34][35]. In accordance, we observed that BALF inflammatory cells infiltration, lung tissue damage as well as AHR were significantly increased and persisted at least for 60 days in the RSV-infected nude mice.…”
Section: Discussionsupporting
confidence: 85%
“…However, in the past decade, it has become clear that the innate immune cells are critical for the development of asthma and related [33][34][35]. In accordance, we observed that BALF inflammatory cells infiltration, lung tissue damage as well as AHR were significantly increased and persisted at least for 60 days in the RSV-infected nude mice.…”
Section: Discussionsupporting
confidence: 85%
“…1) and heterogeneous, since not all determinants are present in all patients or, in a given patient, at all time points. 6,7 We therefore must embrace the concept of a "complex endotype" consisting of several subendotypes as opposed to an endotype that encompasses a single molecular mechanism. 7 Epigenetics and endotypes of allergy and asthma Epigenetic programming during early life influences is crucial for the development of the endotypes of allergic diseases.…”
mentioning
confidence: 99%
“…• Allergies and CRDs often begin early in life and persist throughout the life cycle, affecting all age groups (12,13).…”
Section: Current Challenges Of Allergies and Chronic Respiratory Disementioning
confidence: 99%
“…o Novel diagnostic tools are emerging, allowing better immunologic and functional endotyping of the patient (13,24). Component-resolved diagnosis (CRD) allows the evaluation of the individual sensitization pattern to environmental allergens (25,26).…”
Section: Current Challenges Of Allergies and Chronic Respiratory Disementioning
confidence: 99%